2023
DOI: 10.3390/gels9060440
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Safety of Neauvia Stimulate Injectable Product in Patients with Autoimmune Thyroid Diseases Based on Histopathological Examinations and Retrospective Analysis of Medical Records

Abstract: The aim of this study was to test the effect of hyaluronic acid cross-linked with polyethylene glycol containing micronized portions of calcium hydroxyapatite (Neauvia Stimulate) on both local tissue and systemic consequences, which are crucial from the perspective of long-term safety, in patients suffering from Hashimoto’s disease. This most common autoimmune disease is a frequently mentioned contraindication to the use of fillers based on hyaluronic acid as well as biostimulants based on calcium hydroxyapati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…An additional observation was the use of these preparations in patients diagnosed with Hashimoto's disease. This is another confirmation of the high safety profile and biocompatibility, which was previously demonstrated in histological and in vitro studies published by Kubik et al [9]. What is important, and what has been emphasized, is that there are no substantive or registration contraindications to the use of fillers with PEGylated HA in patients with Hashimoto's disease.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…An additional observation was the use of these preparations in patients diagnosed with Hashimoto's disease. This is another confirmation of the high safety profile and biocompatibility, which was previously demonstrated in histological and in vitro studies published by Kubik et al [9]. What is important, and what has been emphasized, is that there are no substantive or registration contraindications to the use of fillers with PEGylated HA in patients with Hashimoto's disease.…”
Section: Discussionsupporting
confidence: 79%
“…Looking at the available publications, a three-year retrospective study of clinical experience with PEGDE-HA for a range of treatment indications demonstrated long-term results without safety concerns, including no nodules, granulomas, or foreign body reactions [12]. PEGDE-HA has been subjected to extensive molecular, chemical, mechanical and histological characterization, but it should be emphasized that few publications shed diff erent light on the use of tissue fillers among patients with autoimmune diseases [9,[12][13][14][15][16][17]. Clinical results confirm the high safety profile of PEG-cross-linked HA, where, as already mentioned, no granuloma, foreign body reaction or other complications were detected during the 3-year follow-up period [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations